On the pitfalls of measuring aid - Robrecht Renard; Danny Cassimon (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Aid (ODA, Official Development Assistance) statistics are routinely produced by the Development Assistance Committee (DAC) of the OECD on the basis of data provided by bilateral donor agencies and using definitions and guidelines that represent a broad donor consensus. The use of new aid instruments, such as debt relief, has led to several changes and additions to DAC procedures over the years, but the underlying principles and methodology has remained unchanged since the early 1960s. Recent World Bank staff research proposes a more radical departure, introducing the concept of EDA, `Effective Development Assistance'. We use this recent contribution as a starting point to make a more thorough assessment of the methodology used to measure aid in general, and ODA in particular. The methodology is applied to some typical aid instruments, such as tied technical assistance, concessional loans and debt forgiveness. We illustrate that alternative aid measures can make a considerable difference on how we look on aid volumes and trends.
Keywords: F35; O19; 330; development aid; aid accounting; ODA; EDA; Entwicklungshilfe; Statistische Methode; Welt